Paraneoplastic Peripheral Neuropathy in A Case with An Anti-yo Positive Ovarian Carcinoma - Terzi, M.; Türker, H.; Yazici, D.; Akkurt, A.; Onar, M. (My University, 2011)
Paraneoplastic neurological syndromes (PNS) are defined as distant effects of tumors on the nervous system other than metastasis, direct invasion, and metabolic and vascular effects. Despite being rarely encountered diseases of neurology, they are important as early indicators of systemic cancer. There are rare cases reported in the literature of paraneoplastic peripheral neuropathy associated with the development of ovarian malignancy. Our case exhibited positive anti-Yo, ovarian adenocarcinoma, and peripheral neuropathy.
Paraneoplastik Periferik Nöropatisi Olan Anti-Yo Pozitif Over Karsinomu Olgusu
Keywords: Neuropathy; Ovarian Carcinoma; Paraneoplastic